1998
DOI: 10.1002/(sici)1520-6394(1998)8:1+<43::aid-da7>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Extended antidepressant maintenance and discontinuation syndromes

Abstract: Unipolar and bipolar depression are episodic, recurrent illnesses for the majority of patients. Because each episode engenders considerable costs for patients, families, and society, prevention of recurrences has high priority. Numerous studies demonstrate that maintenance antidepressants or mood stabilizing medications are efficacious in preventing recurrences. A review of maintenance studies supports the view that all antidepressants perform significantly better than placebo in preventing recurrences of depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…3,28 Some authors propose tapers as long as 6 to 12 months when complete DC of the agent is desired to allow the receptors to adapt and for earlier detection of recurrent depression symptoms. 4,32 Additionally, for certain agents (eg, irreversible MAOIs), the pharmacodynamic duration of activity may be equally important to consider and more reflective of the offset of activity than drug t 1/2 . To prevent withdrawal, it is generally acceptable to reduce the dose by 25% per week until DC of the medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,28 Some authors propose tapers as long as 6 to 12 months when complete DC of the agent is desired to allow the receptors to adapt and for earlier detection of recurrent depression symptoms. 4,32 Additionally, for certain agents (eg, irreversible MAOIs), the pharmacodynamic duration of activity may be equally important to consider and more reflective of the offset of activity than drug t 1/2 . To prevent withdrawal, it is generally acceptable to reduce the dose by 25% per week until DC of the medication.…”
Section: Discussionmentioning
confidence: 99%
“…1 Studies have been conducted to determine the best methods to decrease the incidence of AD withdrawal and have yielded conflicting results. 1 4 To date, there are no complete guidelines that give guidance on the DC or switching of ADs. The package inserts for these medications usually provide vague and nonspecific recommendations, stating that withdrawal is a potential risk, to taper the medication instead of abruptly discontinuing it and to monitor the patient for any signs of withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous reporting systems are non-interventional with respect to prescribing habits and thus reporting can occur of events that cannot be readily studied for ethical reasons, such as overdoses or inappropriate co-medication. High-quality reports of hitherto unsuspected reactions have led to the detection of signals such as SSRI-electric shock syndrome [8][9][10], and sumatriptanpain activation [11] which would have been hard to detect otherwise. A good understanding of the nature of spontaneous reports is critical to the effective use of KDD tools.…”
Section: E V E L O P I N G a N U N D E R S T A N D I N G O F A N A mentioning
confidence: 99%
“…Studies designed to assess discontinuation syndromes with SSRIs reported rates of about 20% or more. 42,43 Typically, symptoms begin within 24-72 hours of stopping the treatment and last 1-2 weeks, but occasionally much longer. 44 The most commonly reported symptoms were anxiety, paraesthesia, shock-like sensation, balance problems, tremor, seating, insomnia and nightmares.…”
Section: Discontinuation Syndromes With Ssrismentioning
confidence: 99%